The crucial role of end group planarity for fused-ring electron acceptors in organic solar cells. (29th May 2019) - Rech, Jeromy J.; Bauer, Nicole; Dirkes, David; Kaplan, Joseph; Peng, Zhengxing; Zhang, Huotian; Ye, Long; Liu, Shubin; Gao, Feng; Ade, Harald; You, Wei
Abstract : Planar acceptor moieties in FREAs are necessary, as expanding the π–π stacking by only 1 Å disrupts the packing and decreases performance. Abstract : Newly developed fused-ring electron acceptors (FREAs) have proven to be an effective class of materials for extending the absorption window and boosting the efficiency of organic photovoltaics (OPVs). While numerous acceptors have been developed, there is surprisingly little structural diversity among high performance FREAs in literature. Of the high efficiency electron acceptors reported, the vast majority utilize derivatives of 2-(3-oxo-2, 3-dihydroinden-1-ylidene)malononitrile (INCN) as the acceptor moiety. It has been postulated that the high electron mobility exhibited by FREA molecules with INCN end groups is a result of close π–π stacking between the neighboring planar INCN groups, forming an effective charge transport pathway between molecules. To explore this as a design rationale for electron acceptors, we synthesized a new fused-ring electron acceptor, IDTCF, which has methyl substituents out of plane to the conjugated acceptor backbone. These methyl groups hinder packing and expand the π–π stacking distance by ∼1 Å, but have little impact on the optical or electrochemical properties of the individual FREA molecule. The extra steric hindrance from the out of plane methyl substituents restricts packing and results in large amounts of geminate recombination, thus degrading the device performance. Our results show that intermolecular interactions (especially π–π stacking between end groups) play a crucial role in performance of FREAs. We demonstrated that the planarity of the acceptor unit is of paramount importance as even minor deviations in end group distance are enough to disrupt crystallinity and cripple device performance.